Leveraging Deep Learning for Accurate Brain Tumor Detection in Magnetic Resonance Imaging - Venkata Raju (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The research explores the creation and execution of a Convolutional Neural Network (CNN) model for the identification of brain tumors, using deep learning methodologies in neuroimaging. The aim was to enhance tumor detection accuracy, minimize false positives and negatives, and improve fine-grained segmentation and feature extraction through meticulous design and optimization of CNN architecture utilizing Magnetic Resonance Imaging (MRI) and Computed Tomography (CT) scans for deeper insights into tumor pathology. Validation with varied datasets, including cross-validation methods, demonstrated the model's strength and effectiveness, facilitating possible incorporation into clinical procedures. The integration of neural networks with neuroimaging signifies a revolutionary method in redefining brain tumor diagnoses, striving for increased accuracy, efficiency, and individualized healthcare solutions, hence improving patient care and clinical decision-making. This study attempted to construct a viable CNN-based model for brain tumor detection while addressing important problems in the area, including the interpretability of deep learning models in medical imaging and the ethical concerns regarding patient data privacy. This initiative highlights the significance of transparency and ethical issues in the deployment of AI solutions in sensitive healthcare sectors by examining the interpretability of CNN decision-making processes and implementing ethical data management methods. The project's results enhance diagnostic capacities and contribute to the wider discussion on the appropriate integration of artificial intelligence in healthcare, assuring patient-centered and ethically sound technological adoption.